Hubungan Self Awareness Dengan Keterampilan Bermain Futsal Klub Futsalhita Bandung - Albiansyah Pratama; Komarudin Komarudin; Basiran Basiran (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2021)
The SARS-CoV-2 virus outbreak has triggered a series of events. Everyone is forced to do WFH (Work From Home), including the Bandung Futsalhita Club which requires players to do independent training. The facts on the field are that only some players practice in accordance with the training program provided by the coach. Indicating the player's lack of self-awareness, self-awareness is an important factor that players must have. The author conducted research on the relationship of self-awareness with the skills of playing futsal at the Futsalhita Club Bandung. The purpose of this study was to examine the relationship between self-awareness and the skills of playing futsal at the Futsalhita Club Bandung. The method used in this research is descriptive method by means of correlation. The population used is the futsal club Futsalhita Bandung players as many as 20 people. The sample of players taken at the Futsalhita club in Bandung was 11 players with nonprobability sampling with purposive sampling using the Slovin formula. This research instrument uses important areas of self-awareness using the Likert scale and the Game Performance Assessment Instrument (GPAI). The results of this study indicate a high correlation coefficient of 0.920 sig value 0.000 0.05 rejecting Ho and accepting Ha, this shows that there is a significant relationship between self-awareness and the skills of playing futsal for Futsalhita Club players in Bandung.